Case of vector-borne coinfection in a dog - А. B. Mushynskyi; T. M. Suprovych; S. B. Prosyanyi; L. B. Savchuk; T. V. Betlinska (Ukrainian Journal of Veterinary and Agricultural Sciences)
Vector-borne diseases (VBD) in dogs, such as babesiosis, ehrlichiosis, anaplasmosis, and dirofilariasis, pose a significant threat to animal health in many regions worldwide, including Ukraine. These diseases are transmitted through the bites of ectoparasites, such as ticks and mosquitoes. With increasing urbanization, climate change, and population migration, the risk of spreading these diseases is significantly heightened. This article is dedicated to the case analysis of a dog in Ukraine diagnosed with two vector-borne diseases simultaneously, focusing on the clinical manifestations and diagnostic approaches for these conditions. Currently, the prevalence of VBD in dogs in Ukraine is insufficiently studied. There are only sporadic reports of isolated pathogens, with comprehensive information needing to be included. A case of concurrent dirofilariasis and babesiosis in a dog is presented. In the spring of 2024, an 8-year-old intact male German shepherd was brought to a veterinary clinic in Kamianets-Podilskyi due to general weakness. Clinical signs included fever, vomiting, slightly pale mucous membranes, and a mild cough. Following abdominal ultrasound and blood sample collection, anti-inflammatory and antiemetic medications were prescribed. A blood smear revealed Babesia canis and treatment with imidocarb was initiated. However, after a week, the dog's condition did not improve. A repeat blood test detected live microfilariae, and the CaniV-4 test identified antibodies to D. immitis, confirming dirofilariasis. Molecular studies corroborated the diagnosis. Follow-up echocardiography and radiography did not reveal visible adult worms in the heart. The dog was treated with melarsomine and a combination of imidacloprid and moxidectin. Two months later, follow-up blood tests showed no presence of microfilariae, and all blood and biochemical parameters were within normal ranges. The dog was under continuous veterinary supervision for the following months. Overall, there is a noticeable trend in the increase of VBD among dogs in Ukraine, necessitating heightened attention from veterinary services and pet owners. Regular preventive measures, such as ectoparasite control and health monitoring, are crucial for managing the spread of these diseases.